RETRACTED: The Oncolytic Virus in Cancer Diagnosis and Treatment - Cao, Guo-dong; He, Xiao-bo; Sun, Qiang; Chen, Sihan; Wan, Ke; Xu, Xin; Feng, Xudong; Li, Peng-ping; Chen, Bo; Xiong, Mao-ming (Frontiers in Oncology, 2020)
Abstract Cancer has always been a huge threat to human health and survival. Surgery, radiotherapy and chemotherapy could obviously improve the survival of cancer patients, but the most of patients with advanced cancer always have a poor survival or cannot afford the high chemotherapy cost. The emergence of oncolytic viruses provides a new strategy for us to alleviate or even cure malignant tumors. An oncolytic virus can be described as a genetically engineered or naturally existing virus that has an ability of selectively replicating and killing cancer cells without damaging the normal cells. Till now, there has been many kinds of oncolytic virus, such as herpes simplex virus, adenovirus, Coxsackievirus and so on. And they also have different clinical applications for cancer treatment. This review focuses on the clinical application situation and predicts the prospect of oncolytic irotherapy through analyzing the relevant advantages and deficiencies.